Brain Development, Social Context, and Justice Policy - Elizabeth Scott; Natasha Duell; Laurence Steinberg (Washington University Journal of Law & Policy, 2018)
This article examines the role played by biological and psychological factors associated with adolescent criminal activity in the context of justice policy reform and its critics. Scott, Duell, and Steinberg assert that risk-taking behavior in adolescence is not solely associated with biological and psychological immaturity, but rather exists as a dynamic interaction between those factors and the individual social context. This interactive model of juvenile offending supports the trend of treating juveniles differently than adults in the criminal justice system and clarifies how correctional programs are crucial in either undermining or promoting healthy development in adolescents.
Keywords: adolescence; juvenile offender; immaturity; psychology; brain development; social environment; corrections; correctional programs; community-based correctional programs; recidivism; rehabilitation; sentencing; criminology